Kirkenes city as the capital of Barents Region and a symbol of Russian-Norwegian cooperation - Sieradzan, Przemysław (Instytut Politologii UG, Wydawnictwo Adam Marszałek, 2016)
The present paper is dedicated to small multicultural Norwegian city of Kirkenes, which because of its history and geographic location became a symbol of Norwegian- -Russian trans-border cooperation. The text is dedicated to the history of this Arctic city and the beginning, idea and realization of cooperation in Barents Region, which was initiated there in 1993 and the role played by the city in Norway-Russian bilateral relations. Niniejsza praca poświęcona jest niewielkiemu norweskiemu wielokulturowemu miastu Kirkenes, które za sprawą swojej historii i położenia geograficznego stało się symbolem norwesko-rosyjskiej współpracy transgranicznej. Tekst poświęcony jest historii arktycznej miejscowości oraz początkom, idei i realizacji współpracy w Regionie Barentsa, która została zainicjowana właśnie tam w 1993 r., a także roli, jaką przygraniczne miasto odgrywa w norwesko-rosyjskich relacjach dwustronnych.